COMMERCE, ISLAM, AND CULTURAL ORDER IN THE SEVENTEENTH-CENTURY BANTEN SULTANATE: Reassessing the Bazaar Economy - Fahmi Irfani; Ecep Ishak Fariduddin; Muhamad Riza Dzul Fahmi Aly; Mas'udin Syarif (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
This article examines the interplay between commerce, cultural practices, and Islamic values in the seventeenth-century Banten Sultanate. While previous studies emphasize Banten’s position in global trade, insufficient attention has been given to the role of local socio-cultural norms in shaping its economic system. This study addresses that gap by exploring how indigenous traditions and Islamic teachings informed commercial behavior and contributed to Banten’s economic identity.“Using historical methods, the research analyzes primary sources, including European travel accounts (Portuguese, Dutch, and British) and local manuscripts such as Hikayat Hasanuddin. An interdisciplinary framework combining political economy and historical anthropology is employed to interpret the relationship between global trade dynamics and local institutions.“The findings show that Banten functioned as a major regional trading hub for spices, textiles, and other commodities, supported by a bazaar-based system embedded in a hierarchical socio-economic order. Political elites and merchant groups played key roles in regulating trade. Cultural practices such as the Mulud festival and kaget markets demonstrate the integration of economic life with Islamic and Javanese values. Encounters with European traders generated both tensions and adaptive responses within the commercial sphere.